Unlocking workforce readiness through digital employability skills in vocational education Graduates: A PLS-SEM analysis based on human capital Theory - Nur Kholifah; Muhammad Nurtanto; Valiant Lukad Perdana Sutrisno; Nuur Wachid Abdul Majid; Hani Subakti; Rihab Wit Daryono; Achmadi Achmadi (Social Sciences and Humanities Open)
In the context of Industry 4.0, employability skills have become a vital indicator of an individual's readiness for work, particularly in industrial sectors. They are essential for increasing competitiveness, productivity, and long-term career development. However, a significant gap persists among vocational education graduates in Indonesia, where high unemployment rates and skill mismatches pose challenges. This study aims to analyze employability skills among vocational graduates using a human capital investment framework adapted to a digitalization approach. A total of 2587 vocational high school graduates in Yogyakarta, Indonesia, were surveyed using an online questionnaire and selected through exponential snowball sampling. Employability skills were measured through 37 indicators and analyzed using Partial Least Squares Structural Equation Modeling to test both measurement and structural models across 24 hypotheses. The results demonstrate that the proposed empirical model is valid, reliable, and possesses strong predictive power with an R-squared of 0.855 and a Q-squared of 0.605. Digital Communication and Collaboration emerged as the most influential full mediator, effectively linking all exogenous variables to Digital Creativity and Production, highlighting its importance in developing digital productivity and innovation. Several direct relationships were statistically unsupported, including the paths from Technology Adaptation and Specific Software Skills to ICT Resources Integration and Analytical and Problem-Solving Skills to Digital Communication and Collaboration and Digital Creativity and Production. These findings emphasize the importance of structured learning interventions integrating technical training with ICT-based group projects to promote collaboration, digital interaction, and problem-solving. The study contributes practical insights for vocational curriculum development to enhance graduate readiness in the digital labor market.